2006
DOI: 10.4103/0019-509x.25891
|View full text |Cite
|
Sign up to set email alerts
|

Unusual metastasis in colorectal cancer

Abstract: Metastasis from colorectal carcinoma occurs by either lymphatic or hematogenous spread. The most common sites of colorectal metastasis are the liver and lung. Involvement of the skin, muscles and bones are quite rare. The prognosis in such patients is usually poor. Herewith, we are reporting a case of colonic carcinoma who had cutaneous metastasis, muscular involvement and diffuse skeletal metastasis. At the end, she had brain metastasis, but liver and lung involvement was not observed till the end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The occurrence of cutaneous metastatic disease from colorectal cancer is uncommon and typically signifies widespread disease with poor prognosis. Colorectal metastases usually occur within the first 3 years of follow up, and the median survival of patients after the appearance of cutaneous metastatic lesions is 18 to 20 months [2]. Krathen et al reported the overall incidence of cutaneous metastases in various malignancies as 5.3 % and in colorectal cancer as less than 4 % in a met analysis of nine large scale studies assessing patients with cutaneous metastases [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of cutaneous metastatic disease from colorectal cancer is uncommon and typically signifies widespread disease with poor prognosis. Colorectal metastases usually occur within the first 3 years of follow up, and the median survival of patients after the appearance of cutaneous metastatic lesions is 18 to 20 months [2]. Krathen et al reported the overall incidence of cutaneous metastases in various malignancies as 5.3 % and in colorectal cancer as less than 4 % in a met analysis of nine large scale studies assessing patients with cutaneous metastases [1].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous metastasis from colorectal cancer occur less than 4%of patients [1]. The occurrence of cutaneous metastatic disease from colorectal cancer is uncommon and typically signifies widespread disease with poor prognosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…The other unusual metastatic site is skull [5]. Although surgical excision of unusual metastasis such as skin, skull, scapula of colorectal cancer cannot influence the course of the underlying disease, the mean survival time and morbidity can be improved by surgery [12][13][14].…”
Section: Saj Case Reports Issn: 2375-7043mentioning
confidence: 99%
“…Distant cutaneous metastasis occurs by vessel invasion and hematogenous spreading while lymphatic invasion and direct spreading are the most common ways for local cutaneous recurrence [3, 4]. The most common sites of skin metastases are the pelvic region, upper extremities, chest, head and neck region and rarely the glans penis in men [4]. The largest case series of skin metastases from colon cancer in the literature included 80 patients; in 77 cases they were located on the skin of the abdomen [5].…”
mentioning
confidence: 99%